2017
DOI: 10.1038/s41598-017-17132-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Culturomics and Amplicon-based Metagenomic Approaches for the Study of Fungal Population in Human Gut Microbiota

Abstract: Herein, the mycobiota was characterized in fecal samples from sick patients and healthy subjects, collected from different geographical locations and using both culturomics and amplicon-based metagenomics approaches. Using the culturomics approach, a total of 17,800 fungal colonies were isolated from 14 fecal samples, and resulted in the isolation of 41 fungal species, of which 10 species had not been previously reported in the human gut. Deep sequencing of fungal-directed ITS1 and ITS2 amplicons led to the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 59 publications
11
68
2
1
Order By: Relevance
“…4B) in comparison with the estimated Chao1 are the result of the directed sampling strategy that was adopted in the present study. Several authors consider distance levels of 3% to represent species differentiation (Hamad et al, 2017;Passarini et al, 2013;Schloss and Handelsman, 2005;Siles and Margesin, 2016). As expected, the lineage-through-time plots show that the number of expected OTU's decreases with the increase of evolutionary distance ( Supplementary Fig.…”
Section: Diversity and Sampling Effortsupporting
confidence: 55%
“…4B) in comparison with the estimated Chao1 are the result of the directed sampling strategy that was adopted in the present study. Several authors consider distance levels of 3% to represent species differentiation (Hamad et al, 2017;Passarini et al, 2013;Schloss and Handelsman, 2005;Siles and Margesin, 2016). As expected, the lineage-through-time plots show that the number of expected OTU's decreases with the increase of evolutionary distance ( Supplementary Fig.…”
Section: Diversity and Sampling Effortsupporting
confidence: 55%
“…The authors reported that gut mycobiota is mainly dominated by Malassezia, Candida, and Saccharomyces, with S. cerevisiae, M. restricta, and C. albicans identified in 96.8%, 88.3%, and 80.8% of the samples, respectively [16]. Reports from earlier studies using culture-dependent analysis showed that less than 30% of fungal species are present in the human gut [22,23]. Collectively, these studies suggest that gut mycobiome is relatively low in diversity as compared to bacterial communities, and the high prevalence of several fungal species identified across samples further suggested that a core mycobiota may exist in the gut.…”
Section: Fungal Communities In Gutmentioning
confidence: 99%
“…There are two major challenges in applying metagenomics for studying environmental ARGs: (i) in most natural environments, the relative abundance of ARGs is low, which increases the requirement for sequencing depth and cost substantially, and (ii) the assembly of short reads into longer contigs can be challenging for samples from diverse environments (Pärnänen et al, 2016;Martínez et al, 2017). Recent studies have shown that next generation sequencing technologies have high sequencing depth and accuracy to cover complex bacterial communities and resistomes (Perry et al, 2014;Elbehery et al, 2016;Hamad et al, 2017;Crofts et al, 2017;Lanza et al, 2018). However, both methods have some limitations, e.g.…”
Section: The Analysis Of Args With Metagenomics Toolsmentioning
confidence: 99%